2005
DOI: 10.1021/jm040849g
|View full text |Cite
|
Sign up to set email alerts
|

Design And Synthesis of a Novel Potent Myelin Basic Protein Epitope 87−99 Cyclic Analogue:  Enhanced Stability and Biological Properties of Mimics Render Them a Potentially New Class of Immunomodulators

Abstract: A cyclic analogue, [cyclo(87-99)MBP [87][88][89][90][91][92][93][94][95][96][97][98][99] [87][88][89][90][91][92][93][94][95][96][97][98][99] , reported previously for suppressing, to a varying degree, autoimmune encephalomyelitis in a rat animal model, were found in this study to possess the following immunomodulatory properties: (i) they suppressed the proliferation of a CD4 T-cell line raised from a multiple sclerosis patient, (ii) they scored the best in vitro TH2/TH1 cytokine ratio in peripheral blood m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(123 citation statements)
references
References 51 publications
2
121
0
Order By: Relevance
“…Th2/Th1 cytokine ratio in PBMC cultures derived from 13 MS patients, by selectively inducing the secretion of IL-10, (iii) could bind to HLA-DR4, first to be reported for cyclic MBP peptides, and (iv) were more stable to lysosomal enzymes Cathepsin B, D, and H, compared to their linear counterparts [4]. These findings demonstrated that the design and synthesis of linear and cyclic…”
Section: T-cell Clone Created In Vitro From T-cells Isolated From An mentioning
confidence: 58%
See 3 more Smart Citations
“…Th2/Th1 cytokine ratio in PBMC cultures derived from 13 MS patients, by selectively inducing the secretion of IL-10, (iii) could bind to HLA-DR4, first to be reported for cyclic MBP peptides, and (iv) were more stable to lysosomal enzymes Cathepsin B, D, and H, compared to their linear counterparts [4]. These findings demonstrated that the design and synthesis of linear and cyclic…”
Section: T-cell Clone Created In Vitro From T-cells Isolated From An mentioning
confidence: 58%
“…In addition, MBP epitopes are major autoantigens in MS, and the MBP87-99 sequence is an immunodominant epitope [3][4][5]12,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Gln 3 (TCR contact) was not solvent exposed so as to interact with TCR for the antagonist MBP 1-8 [4A] peptide. Knowledge of the relationship of peptide conformation and bioactivity will facilitate the rational design and synthesis The linear peptides were prepared on 2-chlorotrityl chloride resin (CLTR-Cl) using the Fmoc/tBu solid-phase peptide synthetic method [31][32][33][34][35]. The first N a Fmoc (9-fluorenylmethyloxycarboxyl)-protected amino acid Fmoc-Gly-OH was coupled (esterified) to the resin in the presence of diisopropylethylamine (DIPEA) (4.5 equiv, 0.75 mL) in dichloromethane (DCM) in 1 h at RT.…”
Section: Discussionmentioning
confidence: 99%